Effect of increased dietary lysine on growth performance of gilts fed ractopamine HCL (paylean1) in a commercial facility - Neill, C.R.; Hastad, C.W.; Usry, J.L.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,915 gilts (PIC L337 × C22) were used in two 21-d experiments in a commercial research barn to evaluate the effects of lysine rates on pig growth and carcass performance when fed ractopamine HCl. There were 7 replicates per treatment and 21 to 24 pigs per pen in both experiments. In both experiments, treatments included a control diet formulated to 0.65% TID lysine without ractopamine HCl, and diets containing 0.75, 0.85, 0.95, 1.05, and 1.15% TID lysine with 5 ppm ractopamine. There were 983 (initially 217.4 lb) and 932 (initially 226.2 lb) gilts in Exp. 1 and 2, respectively. All diets were based on corn-soybean meal and contained high concentrations of synthetic amino acids (0.325% of L-lysine HCl with added threonine, methionine, and tryptophan) in Exp. 1, but only 0.075% L-lysine HCl in Exp. 2. As lysine increased in the diet, ADG increased and F/G decreased (linear; P<0.05), with the greatest response through 1.05% TID lysine in Exp. 1 and through 0.95% TID lysine in Exp. 2. In both experiments, pigs fed ractopamine HCl had increased (P<0.003) ADG and F/G, compared with performance of pigs fed the control diet. For carcass data, average backfat and FFLI were improved (linear; P<0.03) in Exp. 2 with increasing rates of TID lysine, but were not changed in Exp. 1. These experiments suggest that pigs fed ractopamine HCl require at least 0.95% or 26 g/d of TID lysine and at least 25 g of TID lysine/kg of gain.
Keywords: Swine; Finishing pig; Lysine; Ractopamine HCl